To the intranucleolar translocation of AgNORs in leukemic early granulocytic and plasmacytic precursors - Smetana, Karel; Klamová, Hana; Pluskalová, Michaela; Stöckbauer, Petr; Hrkal, Zbyněk (Histochemistry and cell biology, 2006)
Early leukemic granulocytic and plasmacytic precursors were studied in vitro and in vivo to provide an information on the intranucleolar distribution of AgNORs (silver stained nucleolus organizer regions). In most of these cells AgNORs appeared as clusters of silver stained particles distributed in the whole nucleolar body. On the other hand, in some leukemic early granulocytic precursors, i.e., in myeloblasts and promyelocytes enlarged AgNORs were translocated in the nucleolar peripheral part. In addition, the number of translocated AgNORs at the nucleolar periphery was significantly smaller. Such translocation of a reduced number of AgNORs was easily produced by experimental aging, i.e., starving of cultured leukemic early granulocytic precursors (HL-60 and K562 cells) in vitro and seems to be reversible. Similar translocation of a reduced number of AgNORs was also produced by aging of leukemic plasmacytic precursors. Thus, the translocation of the reduced number of AgNORs to the nucleolar periphery in some blastic leukemic hematopoietic cells might be an useful marker of their aging at the single cell level. However, more studies in this direction are required in the future.
Keywords: buněčné jadérko; Protein Transport; Silver Staining; barvení stříbrem; Nucleolus Organizer Region; HL-60 Cells; Bone Marrow Cells; buněčný cyklus; organizátor jadérka; Cell Cycle; transport proteinů; Plasma Cells; stárnutí buněk; Financing, Organized; HL-60 buňky; Humans; Cellular Senescence; DNA nádorová; K562 Cells; leukemie; RNA nádorová; lidé; Cell Nucleolus; Granulocytes; granulocyty; buňky kostní dřeně; Leukemia; financování organizované; plazmatické buňky; RNA, Neoplasm; DNA, Neoplasm; buňky K562